2017
DOI: 10.1177/0049475517735979
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-aetiologic profile of Onychomycoses in a tertiary care centre in northeast India

Abstract: Onychomycosis refers to fungal nail infection. Despite a clearly diseased appearance, it is often deemed a merely cosmetic problem of relatively minor importance. However, it may result in much psychological or occupational turmoil, diminished self-esteem and resulting reluctance for public interaction. A wide number of factors determine the treatment outcome and its prevalence varies greatly. Our study was conducted between January 2011 and December 2014 in northeast India. Of 243 patients presenting with nai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
6
0
3
Order By: Relevance
“…[15][16][17] Other authors like Banik et al from North east India on the other hand have reported a higher prevalence (65%). 1 There is a wide variation in prevalence rates reported by authors worldwide like 28.3% from Brazil, 56.4% from Tehran, Iran and 60.4% from Ethiopia. [18][19][20] Among the patients included in our study, there was a male preponderance 53.8%, however, there are mixed reports about the prevalence of onychomycosis with respect to gender.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17] Other authors like Banik et al from North east India on the other hand have reported a higher prevalence (65%). 1 There is a wide variation in prevalence rates reported by authors worldwide like 28.3% from Brazil, 56.4% from Tehran, Iran and 60.4% from Ethiopia. [18][19][20] Among the patients included in our study, there was a male preponderance 53.8%, however, there are mixed reports about the prevalence of onychomycosis with respect to gender.…”
Section: Discussionmentioning
confidence: 99%
“…
Onychomycosis is the fungal infection that may involve any component of the nail apparatus as well as the adjoining mesenchymal tissue causing discoloration, thickening or separation of nail from the nail bed. 1,2 Constituting 30% of the cutaneous fungal infections, its incidence varies from 0.5-12% in India and around 5% worldwide. [3][4][5][6][7][8] Onychomycosis is considered to be gender and age-related disease, being commoner in males and older adults in both genders.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hay una notable concordancia en cuanto a la edad de los pacientes que padecen de onicomicosis, El 70,1 % de los casos hallados en nuestro estudio, se encuentran entre 31 y los 65 años, similares a la gran mayoría de las publicaciones contrastadas con cifras que oscilan entre 70,8 % a 89,1 % en el rango etario comprendido ente los 31y 70 años (13)(14)(15)(16) . Es sabida que la edad es un factor de riesgo que aumenta proporcionalmente con el paso de los años (11) .…”
Section: Discussionunclassified
“…Este dato, destaca la importancia del factor externo como la humedad y el contacto prolongado con el agua, descritos como factores que favorecen su incidencia. Otros estudios, que describen esta variable, refieren a las tareas de la casa como actividad principal de los pacientes (12)(13)(14)(15)(16)(17) .…”
Section: Discussionunclassified